Heteroseksual sebagai Politik Identitas: Kajian Sosio-ideologi Larangan Homoseksual dalam Imamat 18:22 melalui Perspektif LGBT - Albert Parsaoran Sihotang (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2023)
AbstractThis article offers a different interpretation of Leviticus 18:22, which has traditionally been seen as a scripture that forbids homosexuality. The Bible outright condemns various sexual orientations such as homosexuality, bisexuality, and bestiality; as a result, the Old Testament portrays heterosexuality as the proper sexual identity. The general reading of texts frequently devolves into pros and contras but leaves little room for other aspects of the text that can allow for a more transformative interpretation. In fact, when texts and the reality of today’s plurality in sexual orientations collide, dominant and judgmental meanings often result. Due to this, socio-ideological studies reread Leviticus 18:22 from an LGBT viewpoint in order to shed light on the Priest’s Tradition’s ideological role in promoting heterosexuality as its identity politics. This analysis gives space to the sociopolitical situation that gives the book its shape, departing fromawareness and skepticism of the existence of other realities that are not described or even repressed in the text (behind the text). Hence, it is hoped that the text’s true meaning, one that liberates prejudice via conversation and creativity, might be recovered.  AbstrakArtikel ini memberikan pembacaan alternatif terhadap teks Imamat 18:22 yang selama ini cenderung dipahami sebagai teks yang mengecam homoseksual. Teks secara eksplisit menolak beragam orientasi seksual seperti homoseksual, biseksual, bestialitas; dan dengan demikian menggambarkan heteroseksual sebagai identitas seksual yang benar dalam Perjanjian Lama. Pembacaan umum terhadap teks acap kali sekadar jatuh pada persoalan pro-kontra, namun tidak memberikan ruang terhadap dimensi lain dari teks yang mungkin memberikan pembacaan yang lebih transformatif. Sebab dalam faktanya, perjumpaan teks dengan realitas keberagaman orientasi seksual di masa kini cenderung memberikan makna yang menghegemoni dan menghakimi. Untuk itu, kajian sosio-ideologis berupaya menguak peran ideologis dari Tradisi Imam yang mempropagandakan heteroseksual sebagai politik identitasnya, serta membaca ulang teks Imamat 18:22 melalui perspektif LGBT. Berangkat dari kesadaran dan kecurigaan akan adanya realitas lain yang tidak digambarkan bahkan dibungkam dalam teks, kajian ini memberikan ruang terhadap situasi sosial-politik yang membentuk teks (di balik teks). Dengan demikian, diharapkan tercapai pemulihan makna dari teks yang membebaskan prasangka secara jujur, dialogis, dan kreatif.